Housing, happiness and capabilities: A summary of the international evidence and models - Dermot Coates; Paul Anand; Michelle Norris (The Open University, Economics Department, 2015)
Housing is not consumed in isolation form other aspects of life and our housing can have important meanings attaching to it. The authors seek to add to the growing literature around capabilities and subjective well-being by drawing out the connections between housing, housing satisfaction and capabilities and by contributing to our understanding of the relationship between housing and life satisfaction. Housing, and the immediate environment, can provide us with a range of freedoms and opportunities that are central to a good life. Good quality, appropriate and affordable housing is not just a source of shelter but can facilitate access to employment and recreational facilities whilst enabling individuals to live healthy and dignified lifestyles and to do so in safety. The objective of this paper is to address two primary questions in this exploration of the international literature: (i) does housing contribute to our assessments of our own utility (or SWB)? and (ii) what factors shape our housing satisfaction and how do these feed through to life satisfaction more generally? To this end, the role of housing satisfaction as a mediating variable is explored. Issues pertaining to habituation, adaptive preferences and the heterogeneity of housing satisfaction are also surfaced here. The paper concludes that there is scope for further empirical research into the connections between housing, housing satisfaction and capabilities, particularly with regard to the operationalization of the capabilities approach in the housing space and an examination of housing and neighbourhood-based functionings (including social indicators) as covariates for housing and life satisfaction.
Keywords: 330; Housing satisfaction; life satisfaction; capabilities approach; behavioural economics